2017
DOI: 10.1021/acs.macromol.7b01539
|View full text |Cite
|
Sign up to set email alerts
|

Fused Perylene Diimide-Based Polymeric Acceptors for Efficient All-Polymer Solar Cells

Abstract: Two polymeric electron acceptors (PFPDI-2T and PFPDI-2FT) based on the fused perylene diimide (PDI) and bithiophene or difluorobithiophene units were synthesized via the Stille polymerization. Both polymers exhibit the strong absorption between 350 and 650 nm, which have the good absorption compensation with the low band gap conjugated polymer in polymer solar cells (PSCs). PFPDI-2T and PFPDI-2FT have the LUMO energy levels of around −4.12 to −4.15 eV, which are comparable with other PDI-based polymers and ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 50 publications
1
61
0
Order By: Relevance
“…147,148 The Stille coupling between trans-1,2-bis(tributylstannyl)ethylene and bromo-substituted PBIs is of even greater synthetic importance as it gives access to vinylene-bridged oligomeric PBIs. The latter compounds represent the key building blocks in the synthesis of fused dimeric PBIs and PBI nanoribbons, 149 in addition to ethylenefused polymers, 150,151 although it should be pointed that the synthetic route for the preparation of the first ethynylene-fused dimeric PBI involved cyclization of alkyne-bridged PTE. 152 Ethenyl-bridged dimeric PBI 134 was synthesized in 88% yield by coupling of bromo-PBI 7g with 0.5 equivalent of 1,2-bis(tributylstannyl)ethylene, using Pd(PPh 3 ) 4 as a catalyst (Scheme 39).…”
Section: Replacement Of Halogen Atoms By Stille Sonoghasira and Glasmentioning
confidence: 99%
“…147,148 The Stille coupling between trans-1,2-bis(tributylstannyl)ethylene and bromo-substituted PBIs is of even greater synthetic importance as it gives access to vinylene-bridged oligomeric PBIs. The latter compounds represent the key building blocks in the synthesis of fused dimeric PBIs and PBI nanoribbons, 149 in addition to ethylenefused polymers, 150,151 although it should be pointed that the synthetic route for the preparation of the first ethynylene-fused dimeric PBI involved cyclization of alkyne-bridged PTE. 152 Ethenyl-bridged dimeric PBI 134 was synthesized in 88% yield by coupling of bromo-PBI 7g with 0.5 equivalent of 1,2-bis(tributylstannyl)ethylene, using Pd(PPh 3 ) 4 as a catalyst (Scheme 39).…”
Section: Replacement Of Halogen Atoms By Stille Sonoghasira and Glasmentioning
confidence: 99%
“…They designed a new acceptor based on FPDI and vinylene unit and achieved a high PCE of 8.59% when blending with PTB7‐Th, which indicated that FPDI was a promising acceptor unit for applications in all‐PSCs. Subsequently, Zhang and co‐workers investigated a series of n‐type polymers based on FPDI and different copolymerized units such as DT, ffDT, 4,7‐dithienyl‐2,1,3‐ benzothiadiazole (DTBT), BDT, T, TT, and Se . All‐PSCs fabricated with PTB7‐Th as the donor and these FPDI‐based polymers as acceptors exhibited remarkable PCEs of 5.35–6.58%.…”
Section: Aromatic Diimides Derived From Pdi or Ndi (Dtcdi Tdi Fpdimentioning
confidence: 99%
“…However, the D1 : 9 a based all‐PSCs showed a higher PCE of 6.39 % with a V oc of 0.73 V, a J sc of 13.47 mA cm −2 , and a FF of 65 % compared with the D1 : 9 b cells with a PCE of 5.35 %. The reduced 9 b performance is likely attributed to the relatively low μ e,SCLC and μ h,SCLC values of the D1 : 9 b blend . This fused PDI unit was further incorporated into the polymer backbone with an electron‐deficient 4,7‐dithienyl‐2,1,3‐benzothiadiazole (DTBT) moiety to afford a novel A‐A type polymer acceptor 10 , which showed greatly improved performance compared with its PDI‐based polymer analog 11 , reflecting the advantage of using two PDI moieties in the polymer backbone.…”
Section: Pdi‐based Polymer Semiconductorsmentioning
confidence: 99%
“…The reduced 9b performance is likely attributed to the relatively low m e,SCLC and m h,SCLC values of the D1:9b blend. [19] This fused PDI unit was further incorporated into the polymer backbone with an electron-deficient 4,7dithienyl-2,1,3-benzothiadiazole (DTBT) moiety to afford a novel A-A type polymera cceptor 10,which showedgreatlyimprovedp erformance compared with its PDI-based polymer analog 11,r eflecting the advantage of using two PDI moieties in the polymer backbone. The highest PCE of 6.23 %w as obtained from D1:10 based all-PSCs, which is the best performance for all-PSCsu sing af used PDI-based A-A type polymer acceptor reported so far.…”
Section: Introductionmentioning
confidence: 99%